A global history of architecture - Ching, Frank, 1943-; Jarzombek, Mark.; Prakash, Vikramaditya (Hoboken, N.J. : Wiley, 2010)
'The award-winning First Edition of A Global History of Architecture was a publishing event that forever changed the way architectural history is viewed and studied. This Second Edition surpasses the first with a lavish new design, illustrated throughout with drawings and photographs in full color, and even more maps and diagrams detailing global interconnections. The signature drawings of Francis D.K. Ching are more informative than ever, updated with scale, annotation, and function added where needed. This revision is sure to remain the most relevant book on the topic'--
'This Second Edition surpasses the first with a lavish new design, illustrated throughout with drawings and photographs in full color, and even more maps and diagrams detailing global interconnections'--
Includes index.
Keywords: Architecture -- History